The Suspects’ Moral Ambiguity in Christie’s Murder on the Orient Express - Friscilla Jesica Goeye; Fransiska Dewi Hastuti (Metathesis: Journal of English Language, Literature, and Teaching, 2025)
Detective fiction delves into the complexities of human nature, questioning justice to reveal the tension between legality and morality. Agatha Christie’s Murder on the Orient Express (1934) stands out as a rich text for literary object study, particularly for its characterization, the moral dimensions of its characters, and the idea of justice in the detective genre. This research uses Barnwell’s concept of Creative Paranoia, combined with Krakowiak & Oliver's theory of Morally Ambiguous Characters, to investigate the twelve suspects as morally ambiguous figures and how their shared actions contribute to the nuance of justice. This research uses a descriptive approach grounded in the creative paranoia framework to explore the suspects' motivation and collective actions. The findings suggest each suspect’s moral retribution stems from personal reasons such as loyalty, love, grief, and honour, which challenged the limits of legal justice. The twelve suspects’ morals are affected by subjective emotion, blurring the line between right and wrong. Through creative paranoia, the suspects’ hypervigilance and reinterpretation of details form a shared justification, positioning themselves as jury and executioner. The study concludes that Christie employs morally ambiguous characterizations to portray justice as a subjective and unstable system, influenced by personal emotions of injustice.